Correlation between results of lamb weaning and milk productivity in the F1 East Friesian and Polish Merino hybrid milking ewes - Mroczkowski S.; Piwczynski D. (Production systems and product quality in sheep and goats, 2001)
The research was carried out on 98 F1 East Friesian x Polish Merino ewes in the 1st to 4th lactation. The ewes were milked mechanically twice a day during a 4-month period, after the weaning of 8-week-old lambs. The influence of the ewes' age on the growth of their offspring before weaning and on their milk production was observed. The production of milk and its basic components was higher in the ewes rearing twins than in those with single lambs. There were higher correlations between the parameters of lambs' growth and development before weaning at the age of 56 days and the quantitative indices of their mothers' milk productivity than between the lambs' growth and the contents of the basic milk components. Litter weight and litter weight gains between birth and the age of 56 days may be an indicator of the ewes' further milking performance.
Meeting of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/09/23-25, Molina de Segura-Murcia (Spain)